Boosting Tech Innovation Ecosystems in Cities : A Framework for Growth and Sustainability of Urban Tech Innovation Ecosystems - Mulas, Victor; Minges, Michael; Applebaum, Hallie (World Bank, Washington, DC, 2015)
Cities are emerging as hubs of technological innovation. This is characterized by an ongoing shift from technology parks in suburban areas, to entrepreneurial activity within cities. There is a global trend of startups in cities like Berlin, Buenos Aires, Mumbai and Madrid. The rise of technology startups in cities is leading to new sources of employment and economic growth, by creation of new businesses and employment categories. Traditional manufacturing and routine cognitive skills jobs are being eroded, and the creation of new sources of employment and growth is vital to maintain competitiveness, reduce poverty, and increase shared prosperity. The growth of tech innovation and entrepreneurship is not equal in all cities. Some cities experience higher, faster, and more sustainable growth than others. This paper discusses research on what factors make tech innovation and entrepreneurship ecosystems grow faster and larger in some cities. The findings point out that the social dimension, or the interpersonal connections and communities, are critical for the growth and sustainability of the ecosystem; and, that networking assets (defined as community building events, skill training events, collaboration spaces, and networking of mentors) are central to this social dimension. This paper includes a) proposed framework for urban technology innovation ecosystems based on this findings; b) testing of the framework in New York, and; c) policy implications of this findings.